Development of protocol for quality control of commercial organic manures and their evaluation - Gowri Priya (Department of Soil Science and Agricultural Chemistry, College of Agriculture, 2008)
The research project entitled “Development of protocol for quality control of commercial organic manures and their evaluation” was conducted at College of Agriculture, Vellayani during 2006-2008, with the objectives of quality evaluation of the major commercial organic manures in Kerala, development of a quality protocol for assessing quality and detecting adulteration in commercial organic manures, studying the mineralization pattern of major nutrients in selected manures and their comparative effect on crop performance. Forty four commercial organic manure products and their raw materials were collected from the manufacturers allover Kerala and their physical, chemical and biochemical characters were analysed. Standard compost manures viz., standard vermicompost, standard coirpith compost and standard city waste compost were prepared at the Instructional Farm, College of Agriculture, Vellayani and their physical, chemical and biochemical characters were analysed. The raw materials viz. bone meal, leather meal and neem cake were mixed in different proportions and the characters of the resulting organic meal mixtures were estimated. Based on these data, a protocol was developed to predict the nitrogen, phosphorus and potassium contents of the organic manures prepared by mixing bone meal, leather meal and neem cake in any ratio. A storage experiment was conducted to study the changes in quality aspects of organic manures during a period of one year. The quality parameters of market samples and the corresponding factory samples of COMs were compared. An incubation experiment was conducted to study the nutrient mineralization pattern of organic manures. A field experiment was carried out to evaluate the performance of selected organic manures using amaranthus variety Arun as test crop. The results of the investigation revealed that none among the forty four commercial organic manures conformed completely to the quality standards specified by the Fertilizer (Control) Amendment Order, 2006, of the Government of India. The colour of COMs varied depending on their raw materials (ingredients) and the odour of COMs varied depending on raw materials and the state of decomposition. The total nitrogen contents of COMs varied from 0.7 per cent to 7.87 per cent. Majority of the COMs had total nitrogen contents between 2.8 per cent and 5.85 per cent. The C/N ratio of COMs varied from 2.86 to 43.18 and only one product viz. SN 4 (Neem cake marketed by TIFFCO Fertilizers & Chemicals) had a ratio more than 20:1. All the COMs contained satisfactory level of total organic carbon. The total phosphorus content varied from 0.12 per cent to 4.57 per cent and the total potassium content in COMs varied from 0.12 per cent to 7.87 per cent. Only eighteen of the COMs had pH in the neutral range and with respect to EC, only three COMs were good for use having EC values less than 4 dS m-1. Based on heavy metal contents, the COMs P.L.meal (PL Agro Technologies Ltd.), Skymeal (Vembanad Chemicals & Fertilizers) and Haritha Super (The Gramakarshaka Fertilizer Company Pvt Ltd.) were found unsuitable for long term application to soil. The standard compost manures did not conform to the specifications of moisture content and bulk density as per Fertilizer (Control) Amendment Order, 2006. The total nitrogen content of SVC was 1.4 per cent, SCC 0.7 per cent and SCWC 2.1 per cent. All the three SCMs recorded C/N ratios below 20. SVC and SCWC had satisfactory levels of total P while SCC was poor in total P. The three SCMs did not contain enough total K to conform to the minimum limit prescribed by the Fertilizer (Control) Amendment Order, 2006. The pH of SVC and SCWC were within the neutral range of 6.5- 7.5, while SCC was more acidic with pH of 3.93. The electrical conductivity of the SCMs ranged from 0.33 to 3.4dS m-1. The total organic carbon contents of SCMs were above 30 per cent. SCMs had heavy metal contents below the maximum limits prescribed by the Fertilizer (Control) Amendment Order, 2006. The analysis of raw materials revealed that leather meal was a good source of nitrogen, bone meal and pressmud were good sources of phosphorus and pressmud was the best source for potassium. The mathematical models developed for predicting the N, P and K contents of any mixture of bone meal, leather meal and neem cake were: N estimated= 3.62088 BM+ 6.58962 LM+ 1.74407 NC+ 4.74391 (BM)x(LM) + 7.8398 (BM) x (NC) – 9.87862 (LM)x(NC), where BM is the proportion of bone meal in the mixture, LM is the proportion of leather meal in the manure and NC is the proportion of neem cake in the mixture. P estimated= 8.41214 BM+ 0.37157 LM+ 0.41953 NC- 2.73548 (BM) x (LM) + 10.15749 (BM) x (NC) – 8.72905 (LM) x (NC) K estimated= 0.38543 BM+ 0.01872 LM+ 1.19747 NC+ -0.04393 (BM) x (LM) + 2.98573 (BM) x (NC) – 5.64704 (LM) x (NC) The model could be used for finding out adulteration of organic manures with inorganic fertilizers to boost their nutrient contents. Different ratios of bone meal, leather meal and neem cake were worked out to prepare organic manures with different levels of N, P and K. The results of the storage study showed that the organic carbon content of organic manures decreased from the initial value during the storage period of one year. The changes in nitrogen, phosphorus, potassium and sodium contents of organic manures showed varying patterns during storage. Comparison of quality of market and factory samples of COMs revealed that the organic carbon and nitrogen content of all the market samples were significantly less than their corresponding factory samples while P and K contents showed varying patterns. The mineralization patterns of major nutrients from the organic manures in incubation experiment indicated that in general, the available nitrogen and phosphorus contents in soils treated with organic manures increased upto 30-45days after incubation and decreased thereafter. The mineralization pattern of potassium from organic manures in soil showed pronounced variation. The treatment with Karshaka Agromeal Grade I (SN 26) recorded higher contents of N, P and K. In the field experiment the highest yield in the first crop was in the treatment with NPK fertilizers + Karshaka Agromeal Grade I. The control treatment with no fertilizers and manures recorded the lowest yield. The application of organic manures was found to improve the quality aspects of the crop. The highest content of available N in soil after harvest of first crop was recorded in T10 (NPK fertilizers + SVC) and lowest available N content was observed in T4. The available phosphorus content after harvest of first crop was highest in T7 (NPK fertilizers + Golden meal) and the lowest value of available P2O5 was observed in T6 (NPK fertilizers +Skymeal). The available potassium content after harvest of first crop was highest in T10 and the lowest content of available potassium was obtained from T14. Application of organic manures was found to raise the pH of the soil in treatment plots. The electrical conductivity of soil was significantly influenced by the different treatments. The highest yield, total dry matter production, total marketable yield and total yield per plant of the second crop was recorded in T7 (NPK fertilizers +Golden meal) and the lowest was in T14. The highest B: C ratio of 1.31 was recorded in T4 and the lowest value was recorded in T14 (absolute control) which had a B:C ratio of 0.90.